The Results of field experiments to determine the effects of the working speed of the machine tractor assembly on the quality of soil cultivation (Mongolian Journal of Agricultural Sciences, 2021)
The main objective was to develop the mathematical models and to analyze the results of field experiments that studied how soil fragmentation changes depending on the speed of the machine-tractor assembly during tillage. There were no significant differences in the analysis of the statistical values of the degree of soil fragmentation measured for each repeated experiment on each variable value of the working speed of the machine tractor assembly and it was done according to the law of normal distribution. We choose the non-linear model, because the mathematical statistical calculations of the experimental data processing proved that a simple linear model was not suitable for our experiment. The regression coefficients were determined after converting the model to a linear function and converting the equation to a linear form. After determining the relationship between the speed of the machine tractor assembly and the degree of soil crumbling, we analyzed based on the graph with certain scale.Хөрс боловсруултын чанарт, угсрааны ажлын хурд нөлөөлөх байдлыг тогтоох хээрийн туршилтын дүнКубота М9000+КПЭ-3.8А угсраагаар хөрсийг сийрүүлэх үед машин тракторын угсраа (МТУ)-ны хөдөлгөөний хурдаас хамаарч хөрсний бутралтын чанар хэрхэн өөрчлөгдөхийг судлах талбайн туршилт явуулж, хэмжилтийн өгөгдлөөр математик загвар гаргах, шинжилгээ хийх зорилго тавив. Угсрааны aжлын хурдны өөрчлөгдөх утга бүр дээр хийсэн туршилт тутамд хэмжсэн хөрсний бутралтын төвшний статистик тоон утгуудыг шинжлэхэд хэт ялгаатай хэмжигдэхүүн байгаагүй бөгөөд тэдгээр нь хэвийн тархалтын хуульд захирагдаж байв. Математик статистикийн тооцооллоос үзэхэд бидний туршилтад энгийн шугаман загвар тохирохгүй байгаа тул шугаман бус загварыг сонгосон. Загварыг шугаман хэлбэрт шилжүүлсний дараа регрессийн коэффициентүүдийг тодорхойллоо. Туршилтаар хэмжиж авсан тоон өгөгдлийг боловсруулж угсрааны ажлын хурд, бутралтын зэргийн хамаарлыг тогтоох, хөрсний бутралтын зэргийн дундаж утгын итгэмжлэх завсрыг тодорхойлох статистик шинжилгээ хийв.Түлхүүр үг: хүчин зүйл, үзүүлэлт, хазайлт, хамаарал, тэгшитгэл, загвар, өөрчлөгдөх хүрээ